Preliminary design of Martian Moons eXploration (MMX). (January 2023) - Kawakatsu, Yasuhiro; Kuramoto, Kiyoshi; Usui, Tomohiro; Sugahara, Haruna; Ootake, Hisashi; Yasumitsu, Ryoichiro; Yoshikawa, Kent; Mary, Stephane; Grebenstein, Markus; Sawada, Hirotaka; Imada, Takane; Shimada, Takanobu; et al.
Abstract: Martian Moons eXploration (MMX) is a mission under development in JAXA in cooperation with NASA, CNES, ESA, DLR to be launched in 2024. This paper introduces the result of its preliminary design and the latest status of the MMX program, putting more weight on the novel part of the mission. The goal of MMX is to reveal the origin of the Martian moons and then to make progress in our understanding of planetary system formation and of primordial material transport around the border between the inner- and the outer part of the early solar system. Additionally, the mission is to survey two Martian moons and return samples from Phobos. Add to those MMX's contribution to the planetary science field, on the growing discussion on the International Space Exploration activities, MMX's contribution to future human Mars exploration is also considered as an essential aspect of the program. Following the system definition study results presented in the previous conference, the following items will be reported in this paper. First, as a result of the comprehensive completion of the Phase-B activities, the preliminary design is completed in coordination with the design of the spacecraft system, mission instruments, and operation plans. This paper describes the proximity and surface operations around Phobos in detail. Second, Phase-C activities have started, incorporating engineering models manufacturing and tests. Those of critical technologies for surface exploration are described in detail. Moreover third, the programmatic aspects, including international cooperation frameworks and the program schedule, are presented. Highlights: Martian Moons eXploration (MMX) is a JAXA's mission to be launched in 2024. MMX achieves the world's first sample return from a Martian moon, Phobos, in 2029. MMX investigates the origin of Martian moons and the planetary formation process. Sample of Phobos contains the ejecta derived from Mars by meteorite impacts. MMX acquires data that contributes to future human Mars exploration.